The difference of the kick start movement in competitive swimming by skill level - Keita, A.; Kurokawa, T.; Deguchi, T.; Nishiyama, K.; Moriki, G.; Adachi, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Kick start (KS) is the starting technique which swimmers set up their rear leg on a back plate of the starting platform, which has been recently introduced in international swimming competitions. It is reported that KS can achieve higher performance than the traditional start in the start phase (Petryaev 2010), but the detailed characteristics of the KS movement has not been clarified. Thus, the aim of this study was to reveal the differences in the KS movement by skill level. Method: After enough warm-up, 6 male university swimmers (upper skilled group), 7 male university swimmers (lower skilled group) and 12 male students majoring physical education (unskilled group) were asked to perform the KS. They were divided into three groups by the 5m time. The KS movement before entering the water was analyzed by 3D-DLT method, and after entering the water was analyzed by 2D-DLT method. Result: In the 5m time and the 5m velocity, there were significant differences between many groups, and there was a tendency that the higher the group`s skill was, the higher these were. In the block time, there was a tendency that the higher the group`s skill was, the shorter the block time was, and a significant difference was especially seen between the upper skilled group and the unskilled group (p<0.05). In the velocity maintenance rate (the entering water velocity/the 5m velocity), the higher the group`s skill was, the higher the velocity maintenance rate was, and there was a significant difference between all the groups (p<0.05). In the time in when the knee angle of the rear leg starts extending, there was a tendency that the higher the group`s skill was, the earlier the time was, and significant difference was especially seen between the upper skilled group and the unskilled group (p<0.05). The unskilled group significantly had a larger entering water angle than other groups (p<0.01), and the lower skilled group significantly showed shorter flight distance than other groups (p<0.05). Discussion: The higher the subject`s skill was, the higher performance of both the 5m time and the 5m velocity were shown by the subjects. Such result was caused because the higher the group`s skill was, the shorter the block time was and the less the speed deceleration was after entering the water. The time in which the knee angle of the rear leg starts extending caused the block time of the upper skill group to be shorter. The entering water angle and the flight distance caused the velocity maintenance rate of the upper skill group to be larger.